2017
DOI: 10.3126/jnhrc.v15i2.18160
|View full text |Cite
|
Sign up to set email alerts
|

Can a Leaflet with Brief Verbal Instruction Teach Nepali Women How to Correctly Contract Their Pelvic Floor Muscles?

Abstract: INTRODUCTIONPelvic organ prolapse (POP) is a common condition for women globally and is one of the most widespread reproductive health problems in Nepal.1,2 POP occurs when the pelvic floor muscles (PFM) and supporting tissues are stretched, weakened or damaged allowing the bladder, uterus or bowel to descend into the vagina. 3Women who have weak or damaged PFMs have 4-11 times the risk of developing a POP when compared to women with good PFM function. 4 Strengthening the PFMs is the first line conservative tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
9
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 11 publications
3
9
0
3
Order By: Relevance
“…Diverse verbal instructions as to how to correctly contract PFMs may influence the displacement of the pelvic floor. However, it is still being debated in the literature as to which recruitment strategy optimizes the displacement of the pelvic floor . For example, should all regions of the pelvic floor musculature around the urethra, vagina, and rectum be mentioned in the instruction; should only one region that is, the anus or the urethra be mentioned or should the transversus abdominis and correct breathing also be utilized?…”
Section: Introductionmentioning
confidence: 99%
“…Diverse verbal instructions as to how to correctly contract PFMs may influence the displacement of the pelvic floor. However, it is still being debated in the literature as to which recruitment strategy optimizes the displacement of the pelvic floor . For example, should all regions of the pelvic floor musculature around the urethra, vagina, and rectum be mentioned in the instruction; should only one region that is, the anus or the urethra be mentioned or should the transversus abdominis and correct breathing also be utilized?…”
Section: Introductionmentioning
confidence: 99%
“…Voluntary contraction of the PFM is performed accurately at less than 50% of the time when training and exercises are performed with verbally guided instructions [3]. Caagbay et al [4] reported that verbal explanations using leaflets on how to contract the PFM were ineffective in subjects with low literacy, limited resources, and or those living in poor settings. The biofeedback method is effective and useful for promoting awareness and control of PFM contraction.…”
Section: Introductionmentioning
confidence: 99%
“…Segundo Talasz et al (2008) A prevalência de IU pode variar entre 24 e 41% em mulheres de 65 anos (BRESEE et al, 2014;GOODE et al, 2008), já em um estudo nacional, foi verificado uma prevalência de 27% em mulheres com idade média de 51 anos (AMARO et al,2009). Em um segundo estudo nacional conduzido por Silva e Lopes (2009) CAAGBAY et al, 2017, JACKSON et al, 2017NEELS et al, 2016aNEELS et al, , 2016b BROWN et al, 1996;LASSERRE et al, 2009;LUO et al, 2017;NYGAARD;BARBER, 2008;ROGERS, 2008).…”
Section: Conhecimento Sobre Os Músculos Do Assoalho Pélvicounclassified
“…A IU acomete mulheres de várias idades, gerando impacto na qualidade de vida e ainda é vista como um "tabu" por essa população (ALMOUSA; VAN LOON, 2017;CARLS, 2007;SHAW et al, 2006 (BØ, 2004;DOSHANI et al, 2007;SMITH et al, 2011). Alguns estudos na literatura demonstram um baixo conhecimento acerca dos MAP entre mulheres (BATISTA, 2017;BERZUK;SHAY, 2015;CAAGBAY et al, 2017;JACKSON et al, 2017;NEELS et al, 2016aNEELS et al, , 2016b. Outros autores já demonstraram que de modo geral a função dos MAP não é boa entre as mulheres (VASCONCELOS, 2017;TALASZ et al, 2005TALASZ et al, , 2008TIBAEK;DEHLENDORFF, 2014).…”
Section: Introductionunclassified